Nursing Care of Diabetes Mellitus with Infection Risk Nursing Problems - Wicaksi, Damon; Agustin, Leni; Maulana Haqiqi, Ahmad (D'Nursing and Health Journal (DNHJ), 2025)
Introduction: Diabetes Mellitus is a progressive chronic metabolic disease. The dangers of Diabetes Mellitus are very great and can allow kidney failure, blindness, and many other complications that can cause death. If not handled properly, it will cause various problems, one of which is the risk of infection. Method: The design used is a case study with clients who experience Diabetes Mellitus with infection risk nursing problems at Dr. H. Koesnadi General Hospital Bondowoso in 2023. Data collection was carried out on 15-18 May 2023 used is interview, observation and physical examination, documentation studies and nursing care form. Result: From the results of the researcher's assessment, not all data obtained from clients can be found according to theory, because it is adjusted from the condition and condition of the client, the diagnosis is in accordance with the theory and results, nursing interventions in principle according to theory, implementation in principle according to theory, evaluation of problems can be resolved in accordance with specific objectives and outcome criteria. Conclusion: It is hoped that clients will always maintain their diet to reduce the risk of hyperglycemia and maintain wound care to avoid the risk of infection.